Analysis of the epidemic situation of the COVID-19 coronavirus infection in Ukraine - Podavalenko, Alla; Malysh, Nina; Zadorozhna, Viktoriya; Zhuk, Kateryna; Zaitseva, Galina; Chorna, Inna (Folia Medica Cracoviensia, 2023)
The epidemic process of COVID-19 in the world developed rapidly. The situation with mor-bidity, despite the establishment of quarantine, the introduction of restrictive anti-epidemic measures, and vaccination, remains difficult. The results of research on the influence of meteorological factors on the dynamics of the incidence of COVID-19, hospitalization, and mortality are ambiguous and contradictory. The purpose of this study is to analyze the indicators of morbidity, hospitalization, and mortality from COVID-19 in Ukraine, and to establish the level of influence of meteorological factors on them. A high variation in morbidity, hospitalization, and mortality rates was observed in Ukraine, in 2020–2021. A total of 3 waves of disease growth were established. The curve of hospitalization indicators of patients with COVID-19 had a correlation dependence on the incidence curve r = 0.766 (р <0.05), the maximum rates of hospitalization and mortality were registered in September–December 2021. A direct strong correlation was established between the frequency of registration of cases of COVID-19 and mortality — r = 0.899 (р <0.05). Most cases of COVID-19 were registered in the cold season, the least in June–August. Inverse correlations of moderate strength were established between the indicators of morbidity, hospitalization, and mortality and air temperature levels (–0.370< r <–0.461). Direct correlations of average strength (0.538< r <0.632) were established with the levels of relative air humidity.
Keywords: coronavirus infection COVID-19; epidemiological situation; morbidity; correlations